A people's hero: Rizal of the Philippines - Reines, Bernard Jacob (New York Praeger, 1971)
A biography of the Philippine national hero--a nineteenth-century preacher of non-violent resistance and the first Asian nationalist to resist colonial oppression.
Bibliography: p. 189.
Keywords: Rizal, Jose, 1861-1896 -- Juvenile literature; Revolutionaries -- Philippines -- Biography -- Juvenile literature